PENGARUH KOMPENSASI, MOTIVASI DAN PENGAWASAN TERHADAP SEMANGAT KERJA KARYAWAN PADA PT. RIAU MEDIA GRAFIKA PEKANBARU - Ferry Arina; Machasin '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted at PT. Graphic Media Riau Pekanbaru address at JalanH. Imam Munandar No. 383 Pekanbaru. The purpose of this study was to analyze the effect of compensation, motivation and supervision of employee morale at PT. Graphic Media Riau Pekanbaru and to examine the effect of compensation, motivation and supervision together on employee morale at PT. Graphic Media Riau Pekanbaru. To achieve these objectives the research carried out by using the sample of 82 people, using Census. Metodeanalisis simultanan test data using partial test. Based on the research results showing that there is a significant effect on compensation, motivation and supervision of employee morale. Based on the above calculation of the value obtained by the value of the coefficient of determination (R2) of 0664. this suggests that the compensation, motivation and supervision simultaneously giving the effect of 66.4% of the employee morale at PT. Graphic Media Riau Pekanbaru. Recommendations that can be submitted is the motivation variable expected with this research the company will pay more attention to the aspects of provision of wages in accordance with the minimum wage Pekanbaru, the guarantee of safety and security in the work, a comfortable work space conditions, the status of the employees who work are clear and demand accountability for what is done because in this indicator would affect the morale of employees in improving their work.Keywords: Compensation, Motivation, Supervision and Morale